Harapan Dan Realitas Pemilihan Kepala Daerah Langsung Di Indonesia - Dawud, Joni (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2005)
Direct election of Local Governor (PILKADA) so far does not give as good impacts as imagined yet due to the unrealised hopes buillt by the concept. The concept is supposed to promote a process of learning on democracy for the people and of course to promote ideal leaders of local governors. However, the economic and social costs caused by the election are not paid off by its result as there are some negative influencing factors, such as the incompetence of the local election commite (KPUD), misuse of power by the ruling and campaigning candidates, the unethical behaviour of refused candidates. The direct election will give its promising benefits when the system, the actors and the people are supportive of ethical, transparent and accountable process of the election.